8.2k views
3 votes
Algebraically show that each of the given combinations are equivalent to the given functions. f(x) – g() is

equivalent to m(x) given:
f(0)
= - 3x + 5; g(x)
- 5x – 7; m(x) = 2x + 12
f(x) – g(x) = (
=
Is f(x) – g(x) equivalent to m(x)? yes

User Beardc
by
5.3k points

1 Answer

6 votes

Answer:


f(x) - g(x) = 2x + 12


m(x) = f(x) - g(x) --- True

Explanation:

Given


f(x) = -3x + 5


g(x) = -5x - 7


m(x) = 2x + 12

Solving (a):
f(x) - g(x)

From the given parameters, we have:


f(x) = -3x + 5


g(x) = -5x - 7

So:


f(x) - g(x)=-3x+5 + 5x + 7

Collect like terms


f(x) - g(x) = 2x + 12

Solving (b) m(x) = f(x) = g(x)?

In (a), we have:


f(x) - g(x) = 2x + 12

And


m(x) = 2x + 12 --- given

By comparison:


m(x) = f(x) - g(x)